Motor-Sensory Recalibration Modulates Perceived Simultaneity of Cross-Modal Events at Different Distances - Parsons, Brent D.; Novich, Scott D.; Eagleman, David M. (Frontiers in Psychology, 2013)
A popular model for the representation of time in the brain posits the existence of a single, central clock. In that framework, temporal distortions in perception are explained by contracting or expanding time over a given interval. We here present evidence for an alternative account, one which proposes multiple independent timelines coexisting within the brain and stresses the importance of motor predictions and causal inferences in constructing our temporal representation of the world. Participants judged the simultaneity of a beep and flash coming from a single source at different distances. The beep was always presented at a constant delay after a motor action, while the flash occurred at a variable delay. Independent shifts in the implied timing of the auditory stimulus towards the motor action (but not the visual stimulus) provided evidence against a central-clock model. Additionally, the hypothesis that the time between action and delayed effect is compressed (known as intentional binding) seems unable to explain our results: firstly, because actions and effects can perceptually reverse, and secondly because the recalibration of simultaneity remains even after the participant’s intentional actions are no longer present. Contrary to previous reports, we also find that participants are unable to use distance cues to compensate for the relatively slower speed of sound when audio-visual events are presented in depth. When a motor act is used to control the distal event, however, adaptation to the delayed auditory signal occurs and subjective cross-sensory synchrony is maintained. These results support the hypothesis that perceptual timing derives from and is calibrated by our motor interactions with the world.